Theoretical Review on Indonesian Academic Legal Education in Conjunction with ASEAN Economic Community Era - Gunadi, Ariawan (UI Scholars Hub, 2014)
Indonesia will be welcoming the ASEAN Economic Community in 2015 as a multilateral agreement to create integrated regions such as: (a) a single market and production base, (b) a highly competitive economic region, (c) a region of equitable economic development, and (d) a region fully integrated into the global economy. These characteristics are interrelated and mutually reinforcing in a sense that overall development would not be complete without total completion of the previous sector. This article discusses the participation of Indonesia as part of ASEAN as a single market and production base, through free flow of services which targets higher education in law. The author researched that Indonesian higher education system still faces issues, especially in legal education. Compared to other states that manages higher education in a relatively guided term, Indonesian legal education is still regulated generally by the government, operated by state and private educational entity, and further trained by profession organization. Indonesian legal education standard has not been supported by proper accreditation bureaucracy from BAN-PT or fair treatment from the government between state and private university. As a result, the quality of Indonesian law graduate still varies. Indonesian legal education is special in nature since it is considered profession and regulated by code of ethic. According to the author, legal education should be integrated with profession organization so that upon graduation, law graduates can directly conduct internship according to their desired profession and compete against ASEAN law graduates.